Determination Levels of Anxiety for Patients Undergoing Endoscopy at Marjan Teaching Hospital in Al- Hillah City - Ali Ahmed Zghair Al-Khafaji (Journal of Global Pharma Technology, 2018)
Background: Upper and lower endoscopy are commonly used to identify and treat numerous gastrointestinal illnesses. These procedures may reason some difficulty for patients such as ache, tachycardia, and in some cases, even a provisional desideration; these difficulties might have unaffected psychological impaction up on the patient health state and may reason a rise in anxiety levels (Previti et al., 2016 Aim of the study: To determine the levels of anxiety for patients undergoing endoscopy. Methodology: Quantitative – Cross sectional design was selected to determine the anxiety levels for patient undergoing endoscopy from the period between 11-October 2016 to 31 August 2017.The digestive system center at Marjan teaching hospital was selected as a risk area to collect the data, purposive sample from (150) patient who scheduled for upper and lower endoscopy were selected. After their agreement to participate in the study. Special anxiety scale adopted after modification. Results: The majority of the study sample 79 (52.7%) were male, 44 (29.3%) between age group (18-27) years old and 50 (33.3%) were with primary education. Most of the study sample 77 (51.3%) recorded moderate anxiety level. Conclusion: Most of the participants recorded moderate anxiety level. Recommendation: Training program may be helpful of the health personnel who work in the clinical area which content all the necessary information related to this procedure, which may prepare them to play their role as education providing the patient with all information, answer all questions and using different educational strategies such as audiovisual taps.Keywords: Determination, Endoscopy, and Anxiety Levels.